The importance of uric acid levels in geriatric patients with respiratory failure under noninvasive mechanical ventilation in the respiratory intensive care unit - Murat Yıldız; Deniz Çelik; Tarkan Özdemir; Güler Eraslan Doğanay; Melek Doğanci; Mustafa Özgür Cırık; Maşide Arı; Kerem Ensarioğlu; Ayşe Cifci; Derya Kızılgöz (BMC Pulmonary Medicine)
Abstract Introduction The respiratory system is critical for gas exchange, with respiratory failure resulting in insufficient oxygen and inadequate removal of carbon dioxide. Serum uric acid (SUA), a byproduct of purine metabolism, rises during hypoxemic conditions and has potential as a prognostic marker in respiratory failure. This study aimed to explore the relationship between SUA levels, mortality, duration of hospital stay, and ICU scores (APACHE II, and SOFA) in geriatric patients receiving non-invasive mechanical ventilation (NIV). Materials and methods We conducted a retrospective analysis of 1109 patients with respiratory failure admitted to the Respiratory Intensive Care Unit (RICU) from 2020 to 2022. We excluded minor patients (under 18 years old), patients with incomplete records, known gout, and dialysis-dependent or SRRT required renal failure. We collected demographics, comorbidities, laboratory findings, APACHE II, and SOFA scores. Patients were divided into two age groups (≥ 65 and < 65). Statistical analysis, including chi-square, regression, and correlation tests, was performed to evaluate the association between SUA and clinical outcomes. Results Patients aged ≥ 65 had significantly higher SUA, creatinine, and BUN levels, as well as longer hospital stays and higher APACHE II and SOFA scores. Elevated SUA levels correlated with increased mortality and NIV requirements in the elderly. Regression analysis confirmed SUA as a predictor of NIV need. Discussion SUA levels are positively associated with worse outcomes in elderly patients with respiratory failure. This study supports previous research findings that hyperuricemia correlates with increased ICU admissions and mortality in respiratory conditions, particularly in older adults who need a noninvasive ventilation (NIV). Conclusion Elevated SUA levels are a valuable prognostic marker for predicting NIV needs and poor outcomes in geriatric patients with respiratory failure. Regular monitoring of SUA could enhance clinical management and improve prognosis in this population.